Plasma progesterone levels following cloprostenol treatment in bovine fetal mummification - Tan, H. S.; Sloss, V.; M. R., Jainudeen (1982)
Progesterone levels before and after cloprostenol (a synthetic analogue of prostaglandin F 2α) treatment for termination of pregnancy complicated by fetal mummification were studied in three imported Jersey heifers. A marked decline in plasma progesterone level was observed within 24 hours after treatment in all cases but cervical dilation did not commence until 48 hours after treatment and was complete within 96 hours. In Cow No. 1, progesterone levels dropped from 6.5 ng/ml before treatment to 1.5, 0.8 and 0.5 ng/ml at 1, 2 and 3 days after teratment. In Cow No.2, daily pre-treatment values ranged from 4.5 to 7.8 ng.ml but were 2.8, 2.0, 1.4 and 0.6 ng/ml for the next 4 days after treatment. In Cow No.3, daily pre-treatment values ranged from 6.8 to 14.7 ng/ml, falling to 1.5, 1.8 and 0.3 ng/ml at 1, 2 and 3 days post-treatment, respectively. Hourly samplings indicated that the decline was most rapid during the first 12 hours after treatment, reaching undetectable levels by the 4th or 5th day. In Cow No.1, the fetal size suggested a 4-month pregnancy while in Cows No.2 and No.3, the fetuses were approximately 6 to 7 months of age.